2014
DOI: 10.2147/dddt.s65678
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-dose pharmacokinetics and pharmacodynamics of evogliptin (DA-1229), a novel dipeptidyl peptidase IV inhibitor, in healthy volunteers

Abstract: PurposeEvogliptin (DA-1229) is a novel, potent, and selective dipeptidyl peptidase IV (DPP-IV) inhibitor in clinical development for the treatment of type 2 diabetes mellitus. This study aimed to investigate the pharmacokinetic and pharmacodynamic profiles and tolerability of evogliptin after repeated oral administration in healthy subjects.Patients and methodsA block-randomized, double-blind, placebo-controlled, multiple-dose, dose-escalation study was performed in a total of 30 subjects. Repeated once-daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 30 publications
2
49
0
Order By: Relevance
“…The PK and PD characteristics of evogliptin were assessed after a single dose in the RI group without diabetes, although these characteristics of linagliptin were previously evaluated under steady‐state conditions . Evogliptin had linear PK characteristics; thus, its PK and PD characteristics could be assessed via a single‐dose study . Although people with T2DM differ from those without diabetes, we assumed that similar results would be obtained for the two patient groups, as DPP‐4 activity has been shown to be an effective surrogate biomarker for the glucose regulatory effects of DPP‐4 inhibitors …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PK and PD characteristics of evogliptin were assessed after a single dose in the RI group without diabetes, although these characteristics of linagliptin were previously evaluated under steady‐state conditions . Evogliptin had linear PK characteristics; thus, its PK and PD characteristics could be assessed via a single‐dose study . Although people with T2DM differ from those without diabetes, we assumed that similar results would be obtained for the two patient groups, as DPP‐4 activity has been shown to be an effective surrogate biomarker for the glucose regulatory effects of DPP‐4 inhibitors …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the efficacy and safety of evogliptin have been shown to be similar to those of sitagliptin in patients with T2DM not adequately controlled by metformin monotherapy. Evogliptin has linear pharmacokinetic (PK) characteristics, and its main route of elimination in humans is the non‐renal route, in association with the human cytochrome P450 3A (CYP3A) enzyme . The fraction excreted unchanged in the urine of evogliptin is 17% to 34% of the administered dose, and the renal clearance (CL R ) rate is ~30% total apparent clearance (CL/F) in humans …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evogliptin is a novel antidiabetic agent that potently and selectively inhibits DPP‐4. Namyi Gu et al reported the pharmacokinetic and pharmacodynamic profiles of evogliptin in healthy subjects . The peak plasma concentration of evogliptin was reached within 4 to 5 hours.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of DPP‐4 activity (>80%) was sustained for over 24 hours, and it provided an increase in postprandial active GLP‐1 levels, 1.5‐ to 2.4‐fold. As a result, evogliptin reduced postprandial glucose by 20% to 35% compared to placebo . And another study reported the pharmacokinetic and pharmacodynamic profiles of evogliptin in renal impairment; the plasma concentration of evogliptin increased 1.98 times in severe renal impairment, but within a therapeutic window .…”
Section: Introductionmentioning
confidence: 99%